Evidence for the Existence of a Multidrug Efflux Transporter Distinct from NorA in Staphylococcus aureus - Kaatz, Glenn W. (American Society for Microbiology, 2000)
A Staphylococcus aureus norA disruption mutant was created by allelic replacement. Exposure of this mutant to norfloxacin produced SA K1748, a derivative with raised fluoroquinolone MICs, found to be the result of a grlA mutation, and raised organic cation MICs. Ethidium and enoxacin uptake was identical in SA K1748 and its parent, but pre-exposure of SA K1748 to organic cations caused a reduction in ethidium uptake as a result of increased efflux. Altered ethidium uptake and efflux, as well as increased MICs of other organic cations, suggest that SA K1748 possesses a non-NorA multidrug efflux transporter that is inducible by its substrates.